2018
DOI: 10.7554/elife.37139
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a critical sulfation in chondroitin that inhibits axonal regeneration

Abstract: The failure of mammalian CNS neurons to regenerate their axons derives from a combination of intrinsic deficits and extrinsic factors. Following injury, chondroitin sulfate proteoglycans (CSPGs) within the glial scar inhibit axonal regeneration, an action mediated by the sulfated glycosaminoglycan (GAG) chains of CSPGs, especially those with 4-sulfated (4S) sugars. Arylsulfatase B (ARSB) selectively cleaves 4S groups from the non-reducing ends of GAG chains without disrupting other, growth-permissive motifs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…Analysis of total extracellular CSPG with CS-56 at early stages of PNN loss, which generally labels CSPGs excluded from PNNs e.g. those found in glial scars [ 54 , 55 ], revealed significant increases in the subiculum but not visual cortex ( p <0.05, p = 0.0818) of 5xFAD mice (Fig. S2A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of total extracellular CSPG with CS-56 at early stages of PNN loss, which generally labels CSPGs excluded from PNNs e.g. those found in glial scars [ 54 , 55 ], revealed significant increases in the subiculum but not visual cortex ( p <0.05, p = 0.0818) of 5xFAD mice (Fig. S2A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Increases in chondroitin sulfate and the chondroitin sulfate proteoglycan versican were identified in more aggressive prostate cancers . Increased C4S has significant consequences for transcription, signaling, metabolism, and proliferation in the prostate and in other tissues …”
Section: Introductionmentioning
confidence: 99%
“…In a tau model of neurodegeneration, plasticity was restored with an antibody against 4-sulfated GAG (Yang S. et al, 2017 ). Our investigation of changes in CS sulfation patterns following both spinal cord injury (Wang et al, 2008 ) and optic nerve crush (Pearson et al, 2018 ) have found a large increase in 4-sulfated GAG chains in the injury site, with little or no change in 6-sulfated GAG chains. In culture, the production of 4-sulfated, but not 6-sulfated GAG chains were increased in astrocytes after treatment with TGF-β (Wang et al, 2008 ).…”
mentioning
confidence: 85%
“…As noted above, 4-sulfated CS is associated with inhibition of axonal outgrowth (Wang et al, 2008;Yoo et al, 2013;Pearson et al, 2018). Both CS-E and DS, which bind to both RPTPσ and NgR1 and 3, contain 4-S GalNAc, but how 4-sulfation affects binding of these sugars to these receptors is yet to be determined.…”
mentioning
confidence: 95%
See 1 more Smart Citation